2020
DOI: 10.3906/vet-1909-54
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of nipple drinker position on water intake, water wastage and drinkingduration of pigs

Abstract: Water determines the life quality of pigs, however, adequate measures need to be taken in order to reduce wastage while the animals are drinking. The current study hypothesized and examined a suitable position at which to fix the nipple drinker to provide sufficient drinking water to pigs while also limiting water wastage. Additionally, this study describes both the drinking pattern and drinking duration of pigs. The height to place the drinker was calculated based on the neck movement of the pigs (neck moveme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 22 publications
1
7
0
Order By: Relevance
“…The current study was conducted at a model swine building located in Gyeongsang National University, Jinju-Si, the Republic of Korea, with 2.9 m width × 5.4 m length × 0.05 m thick roofs as shown in Figure 1 . The GPS coordinates for the site was 35°09′6.26″ N, 128°05′43.838″ E [ 23 ]. The heat conduction is diminished by over 40% while utilizing slatted floors compared to the concrete floors in a naturally ventilated pig barn [ 24 ].…”
Section: Methodsmentioning
confidence: 99%
“…The current study was conducted at a model swine building located in Gyeongsang National University, Jinju-Si, the Republic of Korea, with 2.9 m width × 5.4 m length × 0.05 m thick roofs as shown in Figure 1 . The GPS coordinates for the site was 35°09′6.26″ N, 128°05′43.838″ E [ 23 ]. The heat conduction is diminished by over 40% while utilizing slatted floors compared to the concrete floors in a naturally ventilated pig barn [ 24 ].…”
Section: Methodsmentioning
confidence: 99%
“…Most commercial pig farms choose one or more nipple drinkers for the water supply in one pen rather than bowls. The problem begins if a pig is playing in a nipple drinker; the other pigs have to put up a fight or remain thirsty [ 13 , 105 ]. To provide an adequate water supply for every pig, the drinking duration and number of visits should be monitored.…”
Section: Behavioral and Activity Detectionmentioning
confidence: 99%
“…To provide an adequate water supply for every pig, the drinking duration and number of visits should be monitored. A previous study observed the drinking duration and number of visits to the nipple drinker using a camera, but it was watched by human resources rather than automatically [ 105 ]. However, some studies were conducted to detect the drinking behavior through electronic methods [ 13 , 19 , 108 , 109 ].…”
Section: Behavioral and Activity Detectionmentioning
confidence: 99%
See 2 more Smart Citations